2019
DOI: 10.1139/apnm-2018-0862
|View full text |Cite
|
Sign up to set email alerts
|

Understanding exercise-dependent plasticity of motoneurons using intracellular and intramuscular approaches

Abstract: Spinal motoneurons (MN) exhibit exercise-dependent adaptations to increased activity, such as exercise and locomotion, as well as decreased activity associated with disuse, spinal cord injury, and aging. The development of several experimental approaches, in both human and animal models, has contributed significantly to our understanding of this plasticity. The purpose of this review is to summarize how intracellular recordings in an animal model and motor unit recordings in a human model have, together, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 150 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…Neuroplasticity -mechanism determining reorganization of neuronal chains, e.g. during the motor training after the central nervous system injuries of either cortical or spinal level [14][15][16]. This type includes the functional improvements beyond the frameworks of neurological deficiency recovery, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroplasticity -mechanism determining reorganization of neuronal chains, e.g. during the motor training after the central nervous system injuries of either cortical or spinal level [14][15][16]. This type includes the functional improvements beyond the frameworks of neurological deficiency recovery, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In human investigations, indirect approach has been used to get information about the motor neuron behavior analyzing the response of the motor unit by using surface or intramuscular electromyography. The heterogenous training protocols make difficult to explore and interpret the association between the exercise features and the motor neuron response, so this field is open for further investigations [50].…”
Section: Effect Of Physical Exercise On the Muscle Itself And The Whomentioning
confidence: 99%
“… 3 , 10 , 11 , 12 Extensive evidence has shown that chronic exercise leads to adaptive changes in the membrane properties and excitability of spinal motoneurons in rodents. 3 , 13 , 14 Indeed, recent studies of mouse spinal cord and midbrain neurons have found that chronic exercise induces morphological plasticity and alters their ion channel activity. 12 , 15 , 16 To fully grasp these recent observations and the underlying mechanisms of motor plasticity they are pointing to, a succinct summary of the previous research would be of great utility.…”
Section: Introductionmentioning
confidence: 99%